FA06.06: CLINICAL UTILITY OF YPTNM STAGE GROUPING IN AJCC 8TH EDITION FOR JAPANESE PATIENTS WITH ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Ichikawa, Hiroshi; Sudo, Natsuru; Kosugi, Shin-Ichi; Hanyu, Takaaki; Ishikawa, Takashi; Kano, Yosuke; Muneoka, Yusuke; Otani, Takahiro; Nemoto, Mariko; Bamba, Takeo; Nakagawa, Satoru; Kameyama, Hitoshi; et al.
Abstract: Background: The 8th edition of the American Joint Committee on Cancer staging (AJCC-8th) of esophageal cancer presents independent stage grouping for patients who underwent neoadjuvant therapy followed by esophagectomy (ypTNM). The aim of this study is to elucidate the clinical utility of ypTNM stage grouping in Japanese patients with esophageal squamous cell carcinoma (ESCC). Methods: A total of 146 patients (121 men and 25 women, with a median age of 65 years) who underwent curative esophagectomy following neoadjuvant chemotherapy with cisplatin and 5-fluorouracil (CF) for ESCC between 2005 and 2011 were enrolled in this retrospective study. We compared the distribution of patients and disease-specific survival after esophagectomy (DSS) stratified by ypStage between AJCC-7th and 8th. Additionally, we evaluated the association between clinicopathological features including ypStage in AJCC-8th and DSS. Results: The number of patients classified into ypStage 0/IA/IB/IIA/IIB/IIIA/IIIB/IIIC/IV was 5/1/14/11/35/40/18/18/4 in AJCC-7th, and that classified into ypStage I/II/IIIA/IIIB/IVA/IVB was 27/18/21/58/18/4 in AJCC-8th. According to the revision from AJCC-7th to 8th, ypStage of 85 and 7 patients was up- and down-graded, respectively. Up-grading of ypStage was observed in 83% of patients with ypT4 tumor and in 78% of patients with ypN1–3. The 5-year DSS of ypStage 0/IA/IB/IIA/IIB/IIIA/IIIB/IIIC/IV was 100/100/93/91/75/62/50/28/50% in AJCC-7th, and that of ypStage I/II/IIIA/IIIB/IVA/IVB was 96/83/68/58/28/50% in AJCC-8th. The 5-year DSS of ypStage III was 61% in AJCC-8th comparing to 51% in AJCC-7th, and that of ypStage IV was 31% in AJCC-8th comparing to 50% in AJCC-7th. Univariate analyses identified ypT-8th ( P = 0.028), ypN-8th ( P < 0.001), cStage-8th ( P = 0.006) and ypStage-8th ( P < 0.001) in addition to surgical procedure ( P = 0.027) and histological response ( P = 0.019) as significant prognostic factors for DSS. Among these, multivariate analysis showed that ypStage-8th was a significant independent prognostic factor for DSS ( P < 0.001). Conclusion: ypTNM stage grouping in AJCC-8th can more accurately stratify the prognosis of patients who underwent neoadjuvant CF therapy for ESCC, by classifying patients with residual tumor invasion to adjacent structures and regional lymph node metastasis into more unfavorable prognostic group than that in AJCC-7th. ypStage according to AJCC-8th is the most reliable prognosticator for this disease. Disclosure: All authors have declared no conflicts of interest.